1995
DOI: 10.1007/bf00202662
|View full text |Cite
|
Sign up to set email alerts
|

Gravity induced changes in intracellular potentials in statocytes of cress roots

Abstract: Two glass microelectrodes were inserted from opposite sides of the root cap into statocytes of Lepidium sativum L. immersed in medium with or without cytochalasin D (CD). Intracellular potentials (Eis) of statocytes were measured with reference to an earthed electrode in the bathing solution. In the absence of CD, Ei values were -160 +/- 2 mV (n = 52) in vertical roots. During the recording of Eis, the roots were tilted from the vertical by 45 degrees so that in a tilted root one electrode was on the upper sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…Developmental requirements for PIN3, its localization, as well as the proposed biochemical function for PIN proteins make PIN3 a likely candidate for an efflux component of the lateral auxin transport system. The actin-dependent cycling and rapid relocalization of PIN3 in cells containing gravity-sensing statoliths 22 , taken together with previous findings supporting a direct role of the actin cytoskeleton in gravity perception 23,24 , imply a cellular mechanism for the regulation of asymmetric auxin distribution and differential growth. After a change of the gravity vector, actin-enmeshed statoliths 25 sediment, causing reorganization of the actin cytoskeleton.…”
supporting
confidence: 58%
“…Developmental requirements for PIN3, its localization, as well as the proposed biochemical function for PIN proteins make PIN3 a likely candidate for an efflux component of the lateral auxin transport system. The actin-dependent cycling and rapid relocalization of PIN3 in cells containing gravity-sensing statoliths 22 , taken together with previous findings supporting a direct role of the actin cytoskeleton in gravity perception 23,24 , imply a cellular mechanism for the regulation of asymmetric auxin distribution and differential growth. After a change of the gravity vector, actin-enmeshed statoliths 25 sediment, causing reorganization of the actin cytoskeleton.…”
supporting
confidence: 58%
“…However, gravityinduced changes, if present, have so far remained undetected (Leagué et al, 1997), possibly because of their small size or location to specific cellular microdomains. Changes in root cap cell membrane potentials following gravistimulation have been reported in the literature (Behrens et al, 1985;Sievers et al, 1995). Following gravistimulation of Lepidium sativum roots, Behrens et al (1985) found a transient depolarization of statocytes on the lower side of the root, with repolarization occurring within 60 s to a membrane potential slightly more positive than the original resting potential.…”
Section: The Origin Of Phc Changes In the Columellamentioning
confidence: 88%
“…Statocytes on the upper side showed a slow hyperpolarization following gravistimulation. Sievers et al (1995), also studying L. sativum roots, found that after gravistimulation there was a transient lowering of the membrane potential on both the upper and lower sides after 64 s. In some cases this was preceded by a transient increase. Although changes in membrane potential in response to gravistimulation are not entirely understood, they may play a role in the signaling as well.…”
Section: The Origin Of Phc Changes In the Columellamentioning
confidence: 94%
See 1 more Smart Citation
“…[26][27][28][29] Zygmunt initiated electrophysiological studies aimed at examination of correlation between electrical signals, i.e., ion fluxes, and different physiological processes. Kazimierz Trębacz recalls that technical difficulties were usually a big challenge but they were solved by Zygmunt's ingenious ideas.…”
mentioning
confidence: 99%